Noise-induced interspike interval correlations and spike train regularization in spike-triggered adapting neurons - Urdapilleta, Eugenio (2016)
Fil: Urdapilleta, Eugenio. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina